A curriculum framework for an introductory programme in the national diploma: Engineering at the Vaal University of Technology - Sutherland, G. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Curriculum Studies))-- University of Stellenbosch, 2009